Using Teacher Effectiveness Data for Information-Rich Hiring. (April 2017) - Cannata, Marisa; Rubin, Mollie; Goldring, Ellen; Grissom, Jason A.; Neumerski, Christine M.; Drake, Timothy A.; Schuermann, Patrick
Purpose: New teacher effectiveness measures have the potential to influence how principals hire teachers as they provide new and richer information about candidates to a traditionally information-poor process. This article examines how the hiring process is changing as a result of teacher evaluation reforms.Research Methods: Data come from interviews with more than 100 central office personnel and 76 principals in six urban school districts and two charter management organizations. These sites were systematically sampled based on the amount of time and resources devoted to creating data systems and implementing processes that allow principals access to teacher effectiveness data. In addition to the fieldwork, we also surveyed all principals in six of the eight systems. A total of 795 principals responded to the survey, with an overall response rate of 85%.Findings: The findings suggest that while teacher effectiveness data can be used to inform hiring decisions there is variation in how and the extent to which principals use these measures in hiring. This variation is explained by central office practices as they mediated how principals approached teacher effectiveness data in the hiring process, as well as individual principal characteristics such as principal knowledge and skills, perceived validity of data, and social capital.Implications for Research and Practice: Our results demonstrate ways in which school systems and principals are incorporating teacher effectiveness data into the hiring process. Both principal preparation programs and school systems should focus on ensuring that principals have the skills and resources to use data for human capital decisions.